1091: A Diploma by Roger I on the Reorganisation of Sicily (Transmediterranean History, 2021)
After the Norman conquest of Sicily, Count Roger I founded the Benedictine Abbey of Sant'Agata in Catania in December 1091. To its abbot Ansgerius he entrusted, among other things, the rule over the city of Catania and its surrounding countryside as well as the Muslim population that once lived there. This article contextualises this foundation by reference to the administrative reorganisation of the island of Sicily after the end of Muslim rule and its integration into Roger's realm. At least nominally, Roger seems to have attempted to restore previous settlement structures which had been established under Muslim rule.
Keywords: Catania; conquest; Normans; taxes; dhimma; Muslims under Christian rule; Sicily